Interplay between a crystal's shape and spatiotemporal dynamics in a spin transition material - Slimani, Ahmed (2018)
We investigated by means of optical microscopy (OM) the spatiotemporal features of the thermo-induced spin transition of [Fe(2-pytrz)2{Pd(CN)4}]·3H2O (1) (2-pytrz = 4-(2-pyridyl)-1,2,4,4H-triazole) single crystals having two different shapes (triangle and rectangle). While magnetic and calorimetric measurements, performed on a polycrystalline material, showed the respective average heating and cooling transition temperatures of (Tdown1/2 ∼ 152 K, Tup1/2 ∼ 154 K) and (Tdown1/2 ∼ 160.0 K, Tup1/2 ∼ 163.5 K), OM studies performed on a unique single crystal revealed significantly different switching temperatures (Tdown1/2 ∼ 152 K and Tup1/2 ∼ 162 K). OM investigations showed an interface spreading over all crystals during the spin transition. Thanks to the color contrast between the low-spin (LS) and the high-spin (HS) states, we have been able to follow the real time dynamics of the spin transition between these two spin states, as well as access the thermal hysteresis loop of each single crystal. After image processing, the HS-LS interface's velocity was carefully estimated in the ranges [4.4-8.5] μm s-1 and [2.5-5.5] μm s-1 on cooling and heating, respectively. In addition, we found that the velocity of the interface is shape-dependent, and accelerates nearby the crystal's borders. Interestingly, we observed that during the propagation process, the interface optimizes its shape so as to minimize the excess of elastic energy arising from the lattice parameter misfit between the LS and HS phases. All of these original experimental results are well reproduced using a spatiotemporal model based on the description of the spin-crossover problem as a reaction diffusion phenomenon. © the Owner Societies 2018.